Academic Senate Minutes 2009-05-07 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 4/2/09 approved. GE Program Review Progress Report. Request for endorsement of recommendations for the Center for Culture, Gender and Sexuality from the Senate's Ad-Hoc Diversity Committee approved. New Executive MBA approved. Revision of three Academic Policies: Course Repeat, Withdrawal and Academic Probation, Disqualification and Progress - First Reading. University Strategic Plan – First Reading. Brannen Motion re: amending Robert's Rules Calling for Orders of the Day postponed indefinitely. Good of the Order.